INFLUENCE OF ENTREPRENEURIAL ORIENTATION ON PERFORMANCE OF CONVENTIONAL AND ISLAMIC BANKING IN KENYA - Osore, Saleh Anyango; Ngugi, PhD, Dr. Patrick Karanja; Ogollah, PhD, Dr. Kennedy (European Journal of Business and Strategic Management, 2020)
Purpose: The research was done to establish the influence of entrepreneurial orientation on performance of Conventional and Islamic banking in Kenya. Methods: The study adopted a mixed methods research design based on descriptive, non-experimental and causal approaches. This study considered a census that targeted a population of all the forty three (43) commercial banks that were operational in Kenya as at 31st December 2016. The commercial banks also consist of Islamic banks which offer Shari'ah compliant products and services. This study used a questionnaire as the main instrument for primary data collection. Data preparation started start by coding and cleaning, the primary data obtained from the questionnaires were checked for omissions, legibility and consistency before being coded for analysis. Processed data was analysed by using both descriptive and inferential statistics. Stata version 15 was used for statistical analysis and presentation tables of the results processed in Microsoft excel. Descriptive analysis was done for the observed indicators and presented as frequency, percentages, mean and standard deviation to reveal the distribution trends. The data collected was in the form of observed indicators of larger constructs, thus multivariate dimension reduction techniques (factor analysis) was to be used to form composite latent constructs. The latent constructs generated after dimension reduction was used for statistical modelling. Results: The findings indicated that the mixed effect model fitted with EO as a predictor showed that EO had a significant coefficient estimate at the respondent level (level-1) but there was no significant random effect with EO as a random covariate. A bivariate regression model with considering no random intercepts and no random covariates was fitted to measure the influence of EO on performance only at level 1. The coefficient of EO on performance at level one was found to be 0.824 which implied that increasing the levels of EO by a unit would increase the banks Performance by 0.824 regardless of the banking system. Unique Contribution to Theory, Practice and Policy: The researcher recommended that an increase of the Entrepreneurial Orientation in the banking sector in Kenya is fundamental in the performance of the sector, risk taking and proactiveness elements will go a long way in the growth of the banking industry